Enhancing the security of RCIA ultra-lightweight authentication protocol by using Random Number Generator (RNG) technique - Yasear, Shaymah Akram; Zakaria, Nur Haryani; Omar, Mohd Nizam (Universiti Teknikal Malaysia Melaka, 2017)
This study is an attempt to enhance the security of Robust Confidentiality, Integrity, and Authentication (RCIA) ultra-lightweight authentication protocols.In the RCIA protocol, IDs value is sent between reader and tag as a constant value.This makes RCIA susceptible to traceability attack which lead to the privacy issue. In order to overcome this problem, Random Number Generator (RNG) technique based on Bitwise operations has been used in the tag side.The idea of this technique is to change the IDs of a tag on every query session so that it will not stay as a constant value.The implementation of Enhanced RCIA has been conducted by using a simulation.The simulation provided the ability to show that the operations of RCIA protocol as to compare with the enhanced RCIA.The outcome shows that the enhanced RCIA outperforms existing one in terms of privacy.